2011
DOI: 10.1007/s00128-011-0354-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Metal Bioaccumulation in Three Species of Freshwater Bivalves

Abstract: The metal concentration and body burden of three species of fresh water bivalves, Parreysia cylindrica, Parreysia corrugata and Corbicula striatella were estimated in laboratory experiment after exposure to chronic concentration of arsenic (0.1719 ppm), cadmium (0.23 ppm), copper (0.13 ppm), mercury (0.06 ppm), lead (2.4 ppm) and zinc (5.1 ppm) separately up to 30 days. Dry weight of each animal was used to calculate metal concentrations (μg/g) and the metal body burden (μg/individual). It was observed that zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Studies have been done on metal accumulation in different fish species, other aquatic organisms and sediments, which have clearly demonstrated the aquatic environment is facing metal pollution (Bozcaarmutlu and Arnic, 2007), while the conventional methods for metal monitoring by analyzing the concentration of metals in aquatic organisms is far insufficient for the water quality assessment and aquatic toxicology (Issam et al, 2003;Waykar and Shinde, 2011). The influence of HM the biochemical effect of fish and biomarkers relative have been studied (Golovanova, 2008), the results of this study showed that the mixture of HM may affect the sensitivity and application of antioxidant enzymes as biomarkers and the response of activity of enzymes even in laboratory only can indicate the trends of variation, which should be carefully considered in situ as their values do not conform well with the corresponding metal ion concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have been done on metal accumulation in different fish species, other aquatic organisms and sediments, which have clearly demonstrated the aquatic environment is facing metal pollution (Bozcaarmutlu and Arnic, 2007), while the conventional methods for metal monitoring by analyzing the concentration of metals in aquatic organisms is far insufficient for the water quality assessment and aquatic toxicology (Issam et al, 2003;Waykar and Shinde, 2011). The influence of HM the biochemical effect of fish and biomarkers relative have been studied (Golovanova, 2008), the results of this study showed that the mixture of HM may affect the sensitivity and application of antioxidant enzymes as biomarkers and the response of activity of enzymes even in laboratory only can indicate the trends of variation, which should be carefully considered in situ as their values do not conform well with the corresponding metal ion concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…A. anatina was selected as the native competitor model because unionid bivalves have high conservational interest, and the presence of C. fluminea has been reported to contribute to the decline of their populations (Mouthon and Daufresne, 2010). Mercury was selected as the test substance for this study because: (i) it is a ubiquitous environmental contaminant of global concern due to the negative effects on human and environmental health that it may cause (UNEP, 2013); (ii) it is known to be accumulated by several bivalves including C. fluminea (Ravera et al, 2009;Neufeld, 2010;Waykar and Shinde, 2011); (iii) it causes mortality to freshwater bivalves at concentrations in the low ppm range (Sivaramakrishna et al, 1991) or lower ranges (Keller and Zam, 1991); (iv) it is commonly found in freshwater ecosystems where C. fluminea and A. anatina coexist (B odis et al, 2014;Comero et al, 2014); and (v) more knowledge on its toxic effects are needed to improve environmental and human health risk assessment and safety measures. A multi-parameters approach was selected to assess the toxicity of mercury to test organisms, including mortality and sub-individual biomarkers allowing to assess neurotoxicity, oxidative stress and damage, and energy production alterations because these functions are crucial for individual fitness (Luís and Guilhermino, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On another hand, it is worth of noting that all metals become toxicants while reaching a concentration threshold (Wetzel, 2001). The previous studies have pointed out that metals are indestructible and can be accumulated in the body of organisms (Lau et al, 1998;Waykar, Shinde, 2011), then transferred to higher trophic levels of the food chain (Ikemoto et al, 2008). The toxic effects of metals on living organisms have been well defined and considered as a major threat to aquatic biodiversity (Lanctôt et al, 2016;Millennium Ecosystem Assessment (Program), 2005;Moldovan et al, 2013;Van et al, 2013).…”
Section: Introductionmentioning
confidence: 99%